Industri Rokok Kretek di Kudus Tahun 1914-1950 - Wibawa, Dhanang Satria (Historia Madania: Jurnal Ilmu Sejarah, 2025)
In the 1880s, H. Djamhari mixed tobacco and cloves to produce a product called klobot cigarettes. The cigarettes were then in great demand by the public so that demand from consumers increased rapidly. In 1906, Nitisemito was interested in adopting the business conducted by Djamhari so that in 1914, Nitisemito officially registered his cigarette brand under the name Tjap Tiga Bal and built a factory which was later named Kretek Cigaretten Fabriek M. Nitisemito Koedoes. The business carried out by Nitisemito experienced a very rapid increase, making many people interested in doing the same business. Not only indigenous people, non-indigenous people also made a business in the field of cigarettes as was done by Tjo Kang Hay who founded N.V. Trio. This research aims to find out how the development of the kudus kretek cigarette industry is seen through its historical perspective. After Indonesia gained sovereignty, the government tried to develop the economy by protecting indigenous entrepreneurs. These efforts have not been able to bear fruit due to inadequate human resources and competition with the cigarette industry from non-indigenous companies with large capital and foreign companies that began to enter Indonesia.